A Literature Review for Detection and Projection of Cardiovascular Disease Using Machine Learning - Baral, Sumati; Satpathy, Suneeta; Pati, Dakshya Prasad; Mishra, Pratiti; Pattnaik, Lalmohan (EAI Endorsed Transactions on Internet of Things, 2024)
The heart is a vital organ that is indispensable in ensuring the general health and welfare of individuals. Cardiovascular diseases (CVD) are the major health concern worldwide and a leading cause of death, leaving behind diabetes and cancer. To deal with the problem, it is essential for early detection and prediction of CVDs, which can significantly reduce morbidity and mortality rates. Computer-aided techniques facilitate physicians in the diagnosis of many heart disorders, such as valve dysfunction, heart failure, etc. Living in an "information age," every day million bytes of data are generated, and we can turn these data into knowledge for clinical investigation using the technique of data mining. Machine learning algorithms have shown promising results in predicting heart disease based on different risk parameter. In this study, for the purpose of predicting CVDs, our aim is to appraise and examine the outputs generated by machine learning algorithms including support vector machines, artificial neural network, logistic regression, random forest and decision trees.This literature survey highlights the correctness of different machine learning algorithms in forecasting heart problem and can be used as a basis for building a Clinical decision-making aid to detect and prevent heart disease at an early stage.
Keywords: Support Vector Machine; SVM; Naive Bayes; K-Nearest Neighbor; Coronary artery disease; Arterial pressure; Data Mining; Decision tree